Language Crime by Students in the Communication Process on Campus - Dewi, Resnita; Roni La’biran (Journal of English Education and Teaching, 2023)
This study aims to identify and analyze language crimes that occur in the communication process among students on campus using a forensic linguistic approach. The research method used is a qualitative descriptive method with note-taking techniques. The respondents in this study are students of the Indonesian Christian University of Toraja.  The results of the study indicate that language crimes in communication among students on campus occur in several forms of verbal harassment using animal names such as bai or pig, asu or dog, buaya for crocodile, and balao for rat. In addition, there is also language crime using the bombo or devil. This can affect the mental health and well-being of the victimized students. Lecturers and student organizations have an important role as supervisors and enforcers of regulations, as well as providing education and guidance on language ethics within the campus environment.